The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s10653-009-9255-4
|View full text |Cite
|
Sign up to set email alerts
|

Soil factors associated with zinc deficiency in crops and humans

Abstract: Zinc deficiency is the most ubiquitous micronutrient deficiency problem in world crops. Zinc is essential for both plants and animals because it is a structural constituent and regulatory co-factor in enzymes and proteins involved in many biochemical pathways. Millions of hectares of cropland are affected by Zn deficiency and approximately one-third of the human population suffers from an inadequate intake of Zn. The main soil factors affecting the availability of Zn to plants are low total Zn contents, high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
496
1
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 797 publications
(578 citation statements)
references
References 39 publications
10
496
1
9
Order By: Relevance
“…Half the world's rice paddies are potentially lacking in Zn, with Zn deficient soils amounting for ∼70% of the total arable land in some countries, such as is the case in Pakistan. In Bangladesh the level is ∼23% or equivalent to 2 million hectares (17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Half the world's rice paddies are potentially lacking in Zn, with Zn deficient soils amounting for ∼70% of the total arable land in some countries, such as is the case in Pakistan. In Bangladesh the level is ∼23% or equivalent to 2 million hectares (17).…”
Section: Resultsmentioning
confidence: 99%
“…Zn is the principal micrometerutrient constraining crop production (16), yet it is also a prevalent human nutrient deficiency affecting up to 33% of the global populace (17). The associated health impacts of Zn insufficiency range from stunting, infertility, reduced immunocompetence, and neurobehavioral impairment, while a continued dietary supply must be ensured as storage rates within the body are transient (18).…”
Section: Introductionmentioning
confidence: 99%
“…It was thus concluded that protein in wheat grain could be increased either by low level of Zn as soil application + comparatively higher dose of foliar application or higher dose of Zn through soil application along with higher In calcareous soils, Zn precipitates in unavailable forms for plants, and its uptake and transition to the shoot is inhibited by high concentrations of bicarbonate (Dogar & Van Haj, 1980). However, Zn deficiency in the plants grown in calcareous soils can be recovered fairly readily S: soil treatment; F: foliar spray (4) in rice grains after Zn fertilisation of plants growing on calcareous soil (Singh, 1991).…”
Section: Soil Analysismentioning
confidence: 99%
“…This is particularly the case in cereal production areas and it is estimated that nearly half the soils on which cereals are grown have levels of available Zn low enough to cause Zn deficiency [50 % of soils in Turkey (Eyupoglu et al, 1994), 30 to 70 % of soils in India (Takkar, 1991), 70 % soils in Pakistan (Rashid et al, 1988), 2 m ha of paddy soils in Bangladesh and 8 m ha in China, Japan and the Philippines (Alloway, 2008;2009)]. Since cereal grains have inherently low Zn concentrations, growing them on these potentially Zn-deficient soils further decreases the grain Zn concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Fe availability is indeed the function of solubility rather than of its abundance in the soil (Sahrawat 2000;Guerinot 2001;Hell and Stephan 2003;Pirzadah et al 2010). Zinc deficiency is common in soils with neutral and alkaline pH (calcareous, saline-sodic, and sodic soils), intensively cropped soils, soils with poor drainage, and lowland rice soils (Marschner 1995;Fageria et al 2002;Alloway 2009;Koegel-Knabner et al 2010;Pirzadah et al 2010).…”
Section: Iron and Zinc Uptake Accumulation And Translocation To mentioning
confidence: 99%